Exeter Book Riddles 48 and 59: Trautmann’s “Inscribed Ring” - Orton, Peter (Studia Anglica Posnaniensia, 2025)
Moritz Trautmann, in his 1915 edition of the Exeter Book Riddles, proposed the solution: “Inscribed Ring” to both Riddles 48 and 59; but his arguments have been largely ignored by subsequent editors and commentators, most of whom prefer the older solution: “Chalice” (alternatively “Pyx” or “Paten” for Riddle 48) suggested by Franz Dietrich in an influential article published in 1865. I argue here that Trautmann’s commentary has been partly misread and his case undervalued, and that “Chalice”, or similar Eucharistical objects, were suggested to Dietrich by his own emendation of the metrically deficient verse 11a (dryhtdolg) in Riddle 59 – an emendation that produced a spurious reference to the wounds Christ suffered at the crucifixion. Archaeological evidence in the shape of inscribed precious-metal rings of Anglo-Saxon manufacture supports Trautmann’s solution to both Riddles, which are consequently to be regarded as examples of the same riddling conception of writing as “silent speech” as is shown by the poets of several other Riddles (42 “Cock and Hen”, 47 “Bookmoth”, and 60 “Reed Pen”) in the Exeter Book collection. The idea of an “Inscribed Ring” is, however, indicated too explicitly in both Riddles 48 and 59 to be accepted as the actual solution to either. Comparison with Riddle 47 “Bookmoth”, Riddle 48’s neighbour in the manuscript, suggests that the true solution of all three of these Riddles is the underlying concept of “the written word”.